1967
DOI: 10.1128/jb.94.5.1346-1352.1967
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Streptococcal Cell Wall Antigens In Vivo

Abstract: Specific chemical modification of group A polysaccharide antigen to the A-variant structure was demonstrated in the lymphoid organs of mice by autoradiography by use of radioantibodies specific for these structures. Both antigenic moieties persisted and were still' discerned 10 weeks after injection of the group A cell wall. In rabbit skin, the group A specificity was altered after a prolonged period. Unlike the situation for the mouse, polysaccharide A was not converted to A-variant structure, but another spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

1968
1968
1990
1990

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 8 publications
1
34
0
Order By: Relevance
“…antibodies specific for the polysaecharide or mucopeptide cell wall antigens, their labeling with fluorescein isothiocyanate or 125I, and the fluorescence microscopy or radioantography techniques have been described in detail (4, 9). The tissues from all Swiss-Webster mice, injected intraperitoneally or intravenously with crude sonic extract, were fixed in formalin, paraffin--embedded, and sections 4/z thick prepared.…”
Section: Identification Of Group a Streptococcal Cell Wall Antigens Imentioning
confidence: 99%
“…antibodies specific for the polysaecharide or mucopeptide cell wall antigens, their labeling with fluorescein isothiocyanate or 125I, and the fluorescence microscopy or radioantography techniques have been described in detail (4, 9). The tissues from all Swiss-Webster mice, injected intraperitoneally or intravenously with crude sonic extract, were fixed in formalin, paraffin--embedded, and sections 4/z thick prepared.…”
Section: Identification Of Group a Streptococcal Cell Wall Antigens Imentioning
confidence: 99%
“…(Received for publication 13 December 1967) Studies on the fate of Group A streptococci following phagocytosis have revealed that the ingested streptococci are gradually degraded and lose their serological reactivity with Group A antisera (1,2). 1 In the present studies, the possibility is explored that this degradation is enzymatic in nature and that the loss of serological reactivity is due to the action of an intraphagoeyfic O-Nacetylglucosaminidase.…”
mentioning
confidence: 87%
“…It was thus vital to develop more specific ways for quantitation of levels of bacterial debris in mammalian tissues. Schwab and co-workers performed pioneering studies on qualitative detection of cell wall debris in mammalian tissues using immunofluorescence after injection of well-defined streptococcal cell wall particles ( Ohanian & Schwab 1967). The first semi-quantitative immunoassay for the detection of streptococcal cell wall debris in mammalian tissues was develop more recently (Eisenberg et al 1982).…”
Section: Dormant Bacteria or Non-viablementioning
confidence: 99%